Effects of dietary methyl sulfonyl methane and selenium on laying performance, egg quality, gut health indicators, and antioxidant capacity of laying hens - Kim, Yoo Bhin; Lee, Sang Hyeok; Kim, Da-Hye; Lee, Kyung-Woo (Animal bioscience, 2022)
Objective: This study investigated the effects of dietary methyl sulfonyl methane (MSM) and selenium (Se) on the laying performance, egg quality, gut health indicators, egg yolk Se content, and antioxidant markers in laying hens.Methods: One hundred ninety-two 73-wk-old laying hens were randomly divided into four groups with eight replicates of six hens each. Four diets were prepared in a 2×2 factorial arrangement with or without MSM and Se. The trial lasted for 12 wk.Results: There were no interaction effects or main effects (p>0.05) on laying performance and egg quality. However, feed intake increased in Se-fed hens (p = 0.051) and decreased in MSM-fed hens (p = 0.067) compared with that of hens in the control group. Dietary MSM increased (p<0.05) the ileal villus height and villus height:crypt ratio in hens compared with those receiving the non-supplemented control diet. Dietary MSM and Se did not affect the percentage of short-chain fatty acids in the ileal contents. Dietary Se enriched the Se content in egg yolk compared with that of the non-supplemented control diet (p<0.05). Dietary Se increased (p<0.05) glutathione peroxidase levels in the liver and serum samples compared to the control diet. The total antioxidant capacity in the liver increased (p<0.05) in laying hens that were fed MSM-supplemented diets than in hens fed the control diet. Dietary MSM significantly increased the relative superoxide dismutase levels in serum samples (p<0.05).Conclusion: Supplementation with either MSM or Se independently improved the antioxidant capacity of laying hens. Furthermore, dietary Se produced Se-enriched eggs, but this effect was neither additive nor synergistic with dietary MSM.